2018
DOI: 10.1097/qad.0000000000001917
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy coverage associated with increased co-residence between older and working-age adults in Africa

Abstract: The scale-up of ART has likely led to substantial increases in co-residence between older and working-age adults in Africa. Returns to investments in HIV treatment will be too low, if the social benefits from these changes in living arrangements of older adults are not taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…The largest study used data on over 200 000 individuals from 28 countries. 52 No studies on spillover effects were identified from several high-burden countries such as Eswatini and Botswana, which have among the world’s highest HIV prevalence. Over 90% of studies included at least some data from rural settings in SSA, such as rural KwaZulu Natal in South Africa.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The largest study used data on over 200 000 individuals from 28 countries. 52 No studies on spillover effects were identified from several high-burden countries such as Eswatini and Botswana, which have among the world’s highest HIV prevalence. Over 90% of studies included at least some data from rural settings in SSA, such as rural KwaZulu Natal in South Africa.…”
Section: Resultsmentioning
confidence: 99%
“… 69 71 74 Among the 26 included studies, 16 studies explicitly assessed spillover effects from adults to children (downward spillover effects) 34 35 63 64 68 69 76 77 79–86 and 1 study explicitly assessed spillover effects from working-age adults to older adults (upward spillover effects). 52 Several studies reported spillover effects without fully specifying the recipient of the spillover effect (eg, by grouping together all adult ages in their analytical sample), so that we cannot disentangle the direction of intergenerational spillover effects in those studies. 34 63 68 69 71–75 78 83 85–89 The types of spillover effects that emerged from our analysis were related to (1) wealth and labour market outcomes, (2) health and healthcare utilisation, (3) food security and nutrition, (4) schooling outcomes, (5) caregiving responsibilities, and, lastly, (6) coresidency and relationships.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our hypothesis was that the role of children’s resources may be more pronounced in households where: (1) children were more likely to be affected by the reform, (2) there was a large intergenerational gap in educational attainment between adult children and their parents, and (3) parents were on average older and thus more likely to be ‘dependent’ on the support of children. 30 To do so, we limited the sample to children with at least 9 years of schooling (ie, those primarily affected by the policy reform). For the subset of households with coresident parents and children, we also limited the sample to households where the difference in educational attainment between parents and children was ≥5.5 years (50th percentile), and stratified our model by parental 10-year age groups.…”
Section: Methodsmentioning
confidence: 99%